The role of consumer awareness and prior exposure in preferences for a new regional food label - Liu, J.; Li, Y.; Blare, T. (Elsevier, 2025)
Consumer demand for locally produced food has increased in recent years, driven by both economic and quality-related perceptions. While many studies have examined the impact of established local and regional labels on consumer preferences, little is known about how consumers respond to newly introduced regional marketing labels and how their awareness of such labels evolves over time. This study addressed this gap by investigating consumer valuation of the “SWFL Fresh” label, a recently launched regional food branding initiative. Using a discrete choice experiment across two survey waves, we examined both the development of consumer awareness and the influence of prior exposure on their willingness to pay. In doing so, we offered new insights into how emerging regional labels gain market recognition and economic value. Results indicated that consumers who have previously seen the label are willing to pay 85 % more per pound of SWFL-labeled tomatoes than those with no exposure. However, no significant differences were observed between survey waves, suggesting that awareness may not have increased sufficiently over time. These findings have strong implications for regional branding strategies, highlighting the need for sustained marketing efforts and consumer engagement to enhance label recognition and economic impact.